Rapid Numerical Prototyping of Wind Turbine - Ramesh, Vishal Avinash (Universiti Teknologi PETRONAS, 2020)
Awareness about the significant of sustainable power source for example solar, wind and geothermal as an essential option to non-sustainable power sources has been increment among the world society. Many countries such as Spain, Germany, united states, United Kingdom, japan has been actively involved in the development of renewable energy especially the wind energy which is being used as alternative to supply electrical energy to the people. In Malaysia, wind energy is not widely used the alternative for power generation as the average wind speed is just about 3-6m/s. However, the implementation of wind turbine structures on offshore is being a solution to the problems. In order to increase the development of wind turbine structures in offshore, the performance of the wind turbine should be analysed.